THE ADDITIONAL EFFECT OF CONTRAC-RELAX AND STRETCHING (CSR) WITH HAND POSITION BEHIND THE NECK AND HANDS BEHIND THE BACK BETTER THAN AN EFFECTS OF MASSAGE ADDITIONAL ON ULTRA SOUND (US) AND TRANSCUTANEUS ELECTRICAL NERVE-STIMULATION (TENS) INTERVENTION IN RED - Winaya, I Made Niko (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 1 (2013): Majalah Ilmiah Fisioterapi Indonesia, 2013)
This research aim to know the influence of reduction of pain in bone at patient of FrozenShoulder by comparing gift intervence the US-TENS combined by CRS in hand position rearneck and rear back with the gift intervence the US-TENS very combined by massage. Researcherconduct this research in clinic of physiotherapy private in Bali between September 2011 untilMarch 2012. Sampel amount to 22 one who is taken at random. This research have the characterof the eksperimental with the device of randomized pre-test and post-test design.Group intervence the I of therapy effect yielded is mobilization and pemblokan ofabundant system simpatis activation so that decide the vicious circle of reflex so that shouldermobilization can and improve the nutrisi at network of around shoulder which in the end canlessen the pain in bone shoulder. Group II of therapy yielded is repair of sirkulasi blood causingreduction of pain in bone and relaksasi muscle followed to decrease spasme, others rate irrigatein matrix also mount so that downhill viskositas causing optimal stretching.Data processing and analyse the data processed in manual and constructively StatisticalProgram the for Social Sciene ( SPSS) with the test t-related and test the t-independent by meansof measure used by Verbal Rating Scale (VRS). At intervention of I and II found [by] a pain inbone degradation very having a meaning of shoulder among before and hereafter intervence withthe result P = 0,00 ( P > 0,05). And at difference of degradation of pain in bone of among secondof group do not there are difference having a meaning of where group I got by result 84,77%while group II got by result 60,48%.
Keywords: Contrax relax and stretching, US, TENS, massage, Frozen Shoulder.